2000
DOI: 10.1142/s0218488500000216
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Possibility and Evidence Theory in Civil Engineering

Abstract: This article is devoted to applications of fuzzy set theory, possibility theory and evidence theory in civil engineering, presenting current work of a group of researchers at the University of Innsbruck. We argue that these methods are well suited for analyzing and processing the parameter uncertainties arising in soil mechanics and construction management. We address two specific applications here: finite element computations in foundation engineering and a queueing model in earth work.Keywords: Engineering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Authors like Oberkampf et al 1 demonstrated the potentiality of Evidence Theory to model both epistemic and aleatory uncertainties in the design of engineering systems. Similar examples can be found in the work of Agarwal et al 2 or in the work of Bae et al 3 , Fetz et al 4 He et al 5 and Mourela et al 6 , mainly with applications to structural design. Denoeux proposed a technique to compute an inner and outer approximation of Belief and Plausibility functions 7 .…”
Section: Introductionsupporting
confidence: 64%
“…Authors like Oberkampf et al 1 demonstrated the potentiality of Evidence Theory to model both epistemic and aleatory uncertainties in the design of engineering systems. Similar examples can be found in the work of Agarwal et al 2 or in the work of Bae et al 3 , Fetz et al 4 He et al 5 and Mourela et al 6 , mainly with applications to structural design. Denoeux proposed a technique to compute an inner and outer approximation of Belief and Plausibility functions 7 .…”
Section: Introductionsupporting
confidence: 64%
“…If fuzzy sets are thought of as nested families of sets (i.e., consonant random sets) they can also be handled in random set theory, providing a convenient link between probability theory, possibility theory and fuzzy sets. A random set approach is attractive in the context of geotechnical analysis, as has previously been argued by Fetz et al [2] and Tonon et al [4], because information tends to be scarce and may only be available in the form of interval bounds on unknown quantities or vague testimony of experts. When interval measurements are available from several sources under certain circumstances their combination can be thought of as a (not necessarily consonant) random set.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence there is often considerable uncertainty in predictions of slope stability. Research on stochastic versions of geotechnical models has yielded interesting theoretical insights [1] but is seldom applied in practice because the sample data requirements at a site are so much in excess of what is typically available [2].…”
Section: Introductionmentioning
confidence: 99%
“…As the inner level of problem (30), i.e., equation (29), maximizes the objective which is sought to be minimized for the design optimization in the outer level (i.e., one seeks the design with minimal worst-case), the term anti-optimization has been proposed for this approach.…”
Section: Convex Methodsmentioning
confidence: 99%